RANCANG BANGUN APLIKASI INFORMASI TATA LETAK PERPUSTAKAAN BERBASIS VIRTUAL REALITY - Kania Aulia; Missi Hikmatyar; Ruuhwan (Universitas Palangka Raya, 2023)
Technological developments are developing very quickly, so in this digital era, the use of technology as an effort to improve the delivery of information and promotional media at Perjuangan University uses Virtual Reality technology. Because not all students know or even have never visited the library. This study aims to produce a library layout information application based on Virtual Reality. An Android-based application that can provide information about the layout and usability of the library in a virtual form as if it were in a location using the VR Box tool as the media. The tests were carried out using ISO 25010 quality standards, namely the parameters of functional suitability, portability, and usability using a Likert scale measurement. The results of this study obtained a score of 84% in the